Réponses

Meilleure réponse !
2014-04-30T11:04:01+02:00
Développer : 
A = (3a+4)² - (a-7) (3a+4)
A = (3a)² + 2×3a×4 + 4² + (-a+7) (3a+4)
A = 9a² + 24a + 16 - 3a² - 4a + 21a + 28
A = 9a² - 3a² + 24a - 4a + 21a + 16 + 28
A = 6a² + 41a + 44

Factoriser :
A = (3a+4)² - (a-7) (3a+4)
A = (3a+4) (3a+4) + (-a+7) (3a+4)
A = (3a+4) (3a+4-a+7)
A = (3a+4) (2a+11)

A = (3a+4) (2a+11) = 0 si 3a+4 = 0 ou si 2a+11 = 0
A = (3a+4) (2a+11) = 0 si 3a = -4 ou si 2a = -11
A = (3a+4) (2a+11) = 0 si a = -4/3 ou si a = -11/2
Les solutions de A = 0 sont {-4/3 ; -11/2}